A new brown rot disease of plum caused by Mucor xinjiangensis sp. nov. and screening of its chemical control - Song, Bo; Raza, Mubashar; Zhang, Li-Juan; Xu, Bing-Qiang; Zhang, Pan; Zhu, Xiao-Feng (Frontiers in Microbiology, 2024)
A novel species of Mucor was identified as the causal agent of a brown rot of Prunus domestica (European plum), widely grown in the south of Xinjiang, China. This disease first appears as red spots after the onset of the fruits. With favorable environmental conditions, fruit with infected spots turn brown, sag, expand, wrinkle, and harden, resulting in fruit falling. Fungal species were isolated from infected fruits. A phylogenetic analysis based on Internal Transcribed Spacer (ITS) regions and the Large Subunit (LSU) of the nuclear ribosomal RNA (rRNA) gene regions strongly supported that these isolates made a distinct evolutionary lineage in Mucor (Mucoromycetes, Mucoraceae) that represents a new taxonomic species, herein named as Mucor xinjiangensis. Microscopic characters confirmed that these strains were morphologically distinct from known Mucor species. The pathogenicity of Mucor xinjiangensis was confirmed by attaching agar disk containing mycelium on fruits and reisolation of the pathogen from symptomatic tissues. Later, fourteen fungicides were selected to determine the inhibitory effect on the pathogen. Further, results showed that difenoconazole had the best effect on the pathogen and the strongest toxicity with smallest half maximal effective concentration (EC50) value, followed by a compound fungicide composed of difenoconazole with azoxystrobin, mancozeb, prochloraz with iprodione, pyraclostrobin with tebuconazole, trifloxystrobin with tebuconazole and ethhylicin. Present study provides the basis for the prevention and control of the novel plum disease and its pathogen.